Wireless Energy Harvesting for Cognitive Multihop Wireless Sensor Networks. (27th August 2015) - Nguyen, Van-Dinh; Nguyen, Hieu V.; Shin, Oh-Soon
Abstract : This paper analyzes the performance of cognitive multihop transmissions with wireless energy harvesting in a wireless sensor network. Data transmission between the source and the destination nodes is assumed to occur entirely via several clusters of decode-and-forward relays. The source node and relay nodes are assumed to have the ability to harvest energy from the surrounding signals and to use that harvested energy to forward the information to the next hop. Specifically, we derive an exact closed-form expression to determine throughput and outage probability of the cognitive multihop transmission as a function of an energy harvesting overhead and the interference power constraint at the primary receiver. We assume perfect channel state information at the receivers in order to evaluate the throughput and the outage probability of the cognitive multihop system with wireless energy harvesting.